Estudio de factibilidad para la creación de una empresa procesadora y comercializadora de una bebida energizantea base de pitahaya, cantón Quevedo, Año 2014 - Tituana Cerna, Sandra Elizabeth (2015)
This investment project aims to assess the feasibility of creating producer and marketer of an energy drink based pitahaya, the product will be aimed at consumers of all ages are of high nutritional content, the benefits provided by the pitahaya , will be used as the main raw material. The investment will be directed to the acquisition of machinery, equipment and tools necessary to achieve consolidate the production and marketing operations required by the plant for normal development of the operational activities of production and sale of the product. According to estimates the company "FRUIT ENERGY" as to the projection of the cost of production is 178,301 liters of energy drink for the first year being for the second year 179,494 liters, for the third year 216,573 liters to 217,489 liters for fourth year. Projections with an income of $ 1783301 sales are estimated at a value of $ 356,601.60 for the first year, the second year is 358,987.20, for the third year $ 433,146.24 and with a price of $ 105,453.87 Sales of $ 434,977.92 in the fourth year. According to the financial analysis is expected to profit from the first year for a….